History and availability of salt in the Bajo Huallaga basin. Ways of appropriation of salt mine in a Kichwa community - Valderrama Zevallos, Miguel (2021)
This article explores the links between the Kichwa of the Comunidad Nativa Callanayaku (Bajo Huallaga) and the salt mine of the same name, based on what they say about its use in the past. The stories about the history of this mine highlight several interactions between the Kichwa of Callanayaku with foreign people (employees of a tax company, indigenous people from other indigenous groups, merchants, health personnel) through the circulation of salt, especially commercial exchange. The availability of salt for all these groups is explained by the people in Callanayaku through the control over social relationships in trade networks and the distribution of salt.